First‐recruited motor units adopt a faster phenotype in amyotrophic lateral sclerosis. (9th August 2021) - Weddell, Thomas; Bashford, James; Wickham, Aidan; Iniesta, Raquel; Chen, Maoqi; Zhou, Ping; Drakakis, Emmanuel; Boutelle, Martyn; Mills, Kerry; Shaw, Chris
Abstract : Key points: Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disorder of motor neurons, carrying a short survival. High‐density motor unit recordings permit analysis of motor unit size (amplitude) and firing behaviour (afterhyperpolarization duration and muscle fibre conduction velocity). Serial recordings from biceps brachii indicated that motor units fired faster and with greater amplitude as disease progressed. First‐recruited motor units in the latter stages of ALS developed characteristics akin to fast‐twitch motor units, possibly as a compensatory mechanism for the selective loss of this motor unit subset. This process may become maladaptive, highlighting a novel therapeutic target to reduce motor unit vulnerability. Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder with a median survival of 3 years. We employed serial high‐density surface electromyography (HDSEMG) to characterize voluntary and ectopic patterns of motor unit (MU) firing at different stages of disease. By distinguishing MU subtypes with variable vulnerability to disease, we aimed to evaluate compensatory neuronal adaptations that accompany disease progression. Twenty patients with ALS and five patients with benign fasciculation syndrome (BFS) underwent 1–7 assessments each. HDSEMG measurements comprised 30 min of resting muscle and 1 min of light voluntary activity from biceps brachii bilaterally. MU decomposition was performed by the progressive FastICA peel‐off technique. Inter‐spike interval, firing pattern, MU potential area, afterhyperpolarization duration and muscle fibre conduction velocity were determined. In total, 373 MUs (ALS = 287; BFS = 86) were identified from 182 recordings. Weak ALS muscles demonstrated a lower mean inter‐spike interval (82.7 ms) than strong ALS muscles (96.0 ms; P = 0.00919) and BFS muscles (95.3 ms; P = 0.0039). Mean MU potential area (area under the curve: 487.5 vs . 98.7 μV ms; P < 0.0001) and muscle fibre conduction velocity (6.2 vs . 5.1 m/s; P = 0.0292) were greater in weak ALS muscles than in BFS muscles. Purely fasciculating MUs had a greater mean MU potential area than MUs also under voluntary command (area under the curve: 679.6 vs . 232.4 μV ms; P = 0.00144). These results suggest that first‐recruited MUs develop a faster phenotype in the latter stages of ALS, likely driven by the preferential loss of vulnerable fast‐twitch MUs. Inhibition of this potentially maladaptive phenotypic drift may protect the longevity of the MU pool, stimulating a novel therapeutic avenue. Key points: Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disorder of motor neurons, carrying a short survival. High‐density motor unit recordings permit analysis of motor unit size (amplitude) and firing behaviour (afterhyperpolarization duration and muscle fibre conduction velocity). Serial recordings from biceps brachii indicated that motor units fired faster and with greater amplitude as disease progressed. First‐recruited motor units in the latter stages of ALS developed characteristics akin to fast‐twitch motor units, possibly as a compensatory mechanism for the selective loss of this motor unit subset. This process may become maladaptive, highlighting a novel therapeutic target to reduce motor unit vulnerability.